Does Microfinance Empower Rural Women? – An Empirical Study In Vellore District, Tamil Nadu - Rajendran, K.; Raya, Dr. R. P. (Indian Journal of Finance, 2011)
Microfinance is a powerful tool to reduce poverty and to induce empowerment among rural women so that the rural women may come out of dependency and will move from marginality to centrality. Microfinance plays a vital role in reducing poverty since it paves the way for employment and empowerment, which leads to economic development. Empowerment, poverty reduction and development are interrelated and interdependent. Empowerment leads to economic development, which results in poverty reduction and sustainable development and microfinance, through SHGs, is considered as a tool for empowerment. The purpose of this paper was to critically analyze the real impact of microfinance on empowerment of rural women, and the study was conducted in 2008 in two Blocks in Vellore district in Tamil Nadu with 450 respondents. Simple statistical tools were used to analyse the collected data and conclusions were drawn based on the results. The study concludes that there is an appreciable empowerment in political space than economic empowerment and negligible social empowerment of women as a result of participating in micro finance through SHG programme.